Euro Membership and Fiscal Reaction Functions - Jochen Zimmer; Alfons Weichenrieder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Using fiscal reaction functions for a panel of actual euro-area countries the paper investigates whether euro membership has reduced the responsiveness of countries to increases in the level of inherited debt compared to the period prior to succession to the euro. While we find some evidence for such a loss in prudence, the results are not robust to changes in the specification, as for example an exclusion of Greece from the panel. This suggests that the current debt problems may result to a large extent from pre-existing debt levels prior to entry or from a larger need for fiscal prudence in a common currency, while an adverse change in the fiscal reaction functions for most countries does not apply.
Keywords: H62; E62; H69; 330